The - Neva Widanita; Putri Anisya Pramandani; Ajeng Dian Purnamasari; Septiana Dwi Rakhmawati (Journal of Applied Science for Pharmaceuticals and Health, 2024)
Many women have excess weight and need engaging and enjoyable exercises. Aerobic exercise is a workout aimed at burning fat while improving muscle tone, accompanied by music. This study provided relevant insights into how aerobic exercise affects their issues regarding overweight, body fat increase, and muscle mass reduction. This study used a quasi-experimental method with a Pretest-Posttest Design. Sample determination used Purposive Sampling technique. Hypothesis testing used a paired sample t-test with a sample size of 30 Syifa Studio members. Based on data analysis used paired sample t-test, there was a significant difference in aerobic exercise towards weight loss with a significance value of 0.035 and a t-value of -2.213. Body fat percentage showed a significant difference towards a decrease in body fat percentage with a significance value of 0.030 and a t-value of -2.282, while muscle mass percentage showed a significant difference towards an increase in muscle mass percentage with a significance value of 0.023 and a t- value of 2.401. There was an influence of aerobic exercise on weight loss, body fat percentage, and muscle mass improvement of Syifa Studio members. There is a difference in influence between the group treated with aerobic exercise compared to the control group not treated with aerobic exercise.